2009
DOI: 10.1088/0957-4484/20/17/175705
|View full text |Cite
|
Sign up to set email alerts
|

An effective surface-enhanced Raman scattering template based on a Ag nanocluster–ZnO nanowire array

Abstract: An effective surface-enhanced Raman scattering (SERS) template based on a 3D hybrid Ag nanocluster (NC)-decorated ZnO nanowire array was fabricated through a simple process of depositing Ag NCs on ZnO nanowire arrays. The effects of particle size and excitation energy on the Raman scattering in these hybrid systems have been investigated using rhodamine 6G as a standard analyte. The results indicate that the hybrid nanosystem with 150 nm Ag NCs produces a larger SERS enhancement factor of 3.2 x 10(8), which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 36 publications
3
67
0
Order By: Relevance
“…Chen et al [48] have reported the use of ZnO/Au composite nanoarrays as substrates for surface-enhanced Raman scattering (SERS) based sensing and showed that the density of Au nanoparticles and the morphology of ZnO/Au nanostructures are the two main factors 7 affecting the SERS enhancement. Similar results on SERS enhancement were reported by Deng et al[49] using Ag nanocluster-ZnO nanowire array. Our Raman results showed that increase in fluence to 2x1015 ions/cm 2 resulted in significant increase in the intensity of E 1 (LO) mode.…”
supporting
confidence: 88%
“…Chen et al [48] have reported the use of ZnO/Au composite nanoarrays as substrates for surface-enhanced Raman scattering (SERS) based sensing and showed that the density of Au nanoparticles and the morphology of ZnO/Au nanostructures are the two main factors 7 affecting the SERS enhancement. Similar results on SERS enhancement were reported by Deng et al[49] using Ag nanocluster-ZnO nanowire array. Our Raman results showed that increase in fluence to 2x1015 ions/cm 2 resulted in significant increase in the intensity of E 1 (LO) mode.…”
supporting
confidence: 88%
“…Some examples were listed in Table S3 in SD [28][29][30][31][32][33]. To estimate the detection limit of Ag NCs on ZnO ND system, an optimized ND 2b was used for the detection of CV molecules at low concentrations.…”
Section: Evaluation Of Sers Effect On Ag Ncs On Zno Ndmentioning
confidence: 99%
“…11 Recently, heterostructures of onedimensional nanowires integrated with extraneous nanoparticles were demonstrated to be of great interest due to their excellent detection sensitivity, reproducibility, stability, and biocompatibility. 12,13 Silicon (Si) nanowires have been utilized in bioelectronics, nanoelectronics, optical devices, and energy devices. [14][15][16] The pristine Si nanowires only exhibit moderate Raman sensitivity for molecular detection, and thus proper surface modication or heterostructuring of the nanowires are of particular interest for the purpose of SERS sensing.…”
Section: Introductionmentioning
confidence: 99%